Comparative Analysis of Process Parameter Variations in DGFinFET Device Using Statistical Methods - Roslan A.F.; Salehuddin F.; M Zain A.S.; Mansor N.; Kaharudin K.E.; Ahmad I.; Hazura H.; Hanim A.R.; Idris S.K.; Zaiton A.M.; Zarina B.Z.; Mohamad N.R.; et al. (Institute of Physics Publishing, 2023)
FinFET; Leakage currents; Polycrystalline materials; Polysilicon; Semiconductor doping; Taguchi methods; Threshold voltage; Comparative analysis; Design and optimization; Electrical characterization; International Technology Roadmap for Semiconductors; Optimization approach; Process parameter variations; Subthreshold voltages; Threshold voltages (Vth); Statistical methods